Epigenetic and transcriptional signatures of ex situ conserved golden snub-nosed monkeys (Rhinopithecus roxellana). (September 2019) - Zhang, Du; Hu, Qi; Hu, Yue; Zhang, Yihe; Zhang, Yu; Cui, Peng; Zhou, Yunyun; Liu, Xuefeng; Jiang, Jun; Yang, Linsen; Yu, Huiliang; Yao, Hui; et al.
Abstract: Extremely endangered wildlife can be effectively protected by ex situ conservation programs. Despite that, the effects of human activity on the health of captive populations are still unclear. Using reduced representation bisulfite sequencing and RNA-seq, we assessed epigenetic and gene transcriptional variations between different types of human intervention ("Custodial" and "Sanctuary" groups) and a "Wild" group of golden snub-nosed monkeys ( Rhinopithecus roxellana ), which is one of the most endangered primates worldwide. Consequently, we found striking genome-scale divergence of both DNA methylation and gene expression for the Custodial group, which agreed with stronger human interventions on the food supply and management of the group. KEGG pathway analyses indicated that the differentially expressed genes were enriched in a wide range of physiologically functional pathways, most of which are involved in immune and metabolic functions. In particular, a group of core genes in autophagy related pathways, e.g., ATP6V0A1 and PPM1D, were both differentially expressed and methylated. Our findings revealed that the ex situ conserved golden snub-nosed monkey exhibited significant epigenetic and transcriptional adaptation to human intervention, thereby may provide a foundation for future biomarker development that can be used to evaluate the unintended risks of ex situ conservation programs for endangered animal species.